Superficial Characteristics of Women in Online Media Tiktok - Refika Mastanora; Elfira Maya Sari (State Institute of Islamic Studies Batusangkar, 2023)
The views and images of women in the media can vary greatly, depending on the context and type of media involved. However, there are several common patterns in the representation of women in the media, including: Traditional stereotypes: The media still often portrays women in traditional stereotypes, such as domestic roles as mothers or homemakers, or as objects of sexualization conforming to narrow beauty standards. Narrow representation: Women in the media are sometimes depicted in limited roles, merely serving as embellishments to stories involving male main characters. Objectification: Media frequently treats women as objects, focusing on their physical appearance and sexuality rather than their abilities or personalities. Violence and injustice: Certain types of media tend to exploit portrayals of violence or injustice experienced by women, without adequately addressing these issues. Based on this background, the researcher is interested in identifying the characteristics of women in the online media Tiktok, as Tiktok is a trending social media platform in its utilization.